Pengawasan dan Penindakan sebagai Upaya Perlindungan Hukum terhadap Dana Masyarakat yang Disimpan di Lembaga Koperasi (Studi Kasus di Ksu Banjar Negari, Kabupaten Gianyar) - Ni Komang Nanda Permata Dewi; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Preferensi Hukum, 2022)
This study aims to discuss the legal protection of public funds stored in cooperative institutions and cooperative action against cooperative customers who default in terms of borrowing cooperative funds. Cooperatives as a form of the business entity have an important position for empowering and strengthening the people's economy. Based on equal rights and obligations in carrying out certain businesses that intend to meet the various needs of the members. The research method used is the empirical method. Regarding the protection of citizen funds by irregularities in cooperative institutions, there is no legal certainty. Default has legal consequences for those who run it and poses a risk with the emergence of parties who feel that their rights have been harmed to prosecute parties who have defaulted in order to submit compensation, so by In the law, it is desirable that no one party feels the loss due to the default. The first sanction against cooperatives that apply legal protection to cooperative customers is to provide a letter of introduction by the cooperative regarding what the debtor is doing.